Allelic diversity of simple sequence repeats among elite inbred lines and mutants of cultivated Sunflower (Helianthus annuus L.) - *Prashanth babu, H ., Nadaf, H. L and Boraiah, K. M. (Electronic Journal of Plant Breeding, 2012)
Ten simple sequence repeat (SSR) markers were used to evaluate genetic relationships in a set of twelve parental lines of sunflower representing the genetic stock, including restorers, maintainer and mutant lines of the classical cytoplasmic male sterility. A total of 26 loci were detected among the twelve genotypes. Of this, 23 loci were polymorphic for the inbred lines investigated. Average number of bands and polymorphic bands per primer were 2.6 and 2.3 respectively. NTSYS-pc (ver 2.02) was used to calculate the jaccard’s similarity coefficients. Genetic dissimilarity estimates based on simple matching coefficient revealed more genetic diversity among the genotypes tested. The greatest genetic diversity was observed between the RHA-851A and RHA-265 (0.87) followed by RHA-851A and R-298 (0.857) and more similarity was between RHA-265 and R-298 (0.08). Unweighted pair group method with arithmetic mean (UPGMA) cluster analysis grouped the 12 genotypes into four groups at 0.74 similarity coefficient.